HEALTH BENEFITS OF CONJUGATED LINOLEIC ACID - Mila Arapceska; Jovanka Tuteska; Zehra Hajrulai-Musliu; Risto Uzunov (Trakya University, 2019)
In recent years, the bioactive compounds present in food, even though in minor amounts, have received increased attention because they may have an important nutritional role. Conjugated linoleic acid (CLA) is a generic term used to describe a group of geometric and positional isomers of linoleic acid with a conjugated double bond mainly at carbons 9 and 11 or 10 and 12. Milk fat is the richest natural source of CLA. The CLA-isomers are produced via biohydrogenation of the unsaturated fatty acids presented in animal feed into saturated by rumen bacteria and by the enzymatic activity of the Δ9-desaturase in the mammary gland. Numerous physiological properties have been attributed to CLA including action as an antiadipogenic, antidiabetogenic, anticarcinogenic, antiatherosclerotic agent and chronic inflammatory diseases. In addition, CLA has effects on bone formation and the immune system as well as fatty acid and lipid metabolism and gene expression in numerous tissues. Because potential health benefits have been associated with dietary consumption of CLA, enhancement of CLA concentrations in meat and milk is an important objective in nutrition research.
Keywords: milk fatty acids; CLA; human health